ORGANIZATIONAL SOCIAL RESPONSIBILITY IN STRENGTHENING MEMBER PERFORMANCES - Hilmi Nur Fauzan; Iwan Iwan; Natalia Willy Harto; Velissa Nyctagina; Suherdi Suherdi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
Every organization must have a work program and vision and mission in carrying out its duties and activities. To carry out the work program, the organization must have responsibilities from the members of the organization. In this study, researchers conducted research on the Management Student Association of the State University of Jakarta which aims to analyze the organizational responsibilities of the Student Association Management Organization of the State University of Jakarta in improving the work program and performance of its members. This research uses a qualitative approach with a case study method to gain an in-depth understanding of organizational responsibility and its impact on member performance. Data were collected through in-depth interviews and participatory observation. The results showed that HIMA Management has a strong responsibility towards its members. The organization provides personal development programs, training, academic activities, and social support that contribute to improved member performance.